Caracterización ultrasonográfica de los órganos abdominales y pélvicos del oso perezoso de dos dedos (Choloepus hoffmanni) criados en cautiverio - Salgado N., Sergio (2024)
Adult specimens of Choloepus hoffmanni, 14 females and 5 males, bred in captivity, in apparent good health, were used to perform an ultrasound evaluation of the abdominal and pelvic organs using the ESAOTE MyLab One Vet ultrasound scanner with SC3123 convex transducer, 9-4 MHz. The results indicate that the ultrasound characteristics and dimensions of the abdominal organs of C. hoffmanni are very similar to those observed in the tamandua and other companion animals of similar size; however, it differs from other species in that the liver has less echogenicity than the kidney, the stomach is large, and the testicles are located intra-pelvically; and the fullness of the stomach and urinary bladder can affect the topographic location and visualization of other abdominal organs.